Abril 2023 (Abstracta, 2023)
Artigos publicados - P009-2023 à P040-2023Artigos aceitos - A01-2023Correções - C01-2023Defesas de Dissertações do IFGW - D002-2023 à D004-2023Defesas de Teses do IFGW - T003-2023